USO DE SISTEMAS INTEGRADOS DE GESTÃO EMPRESARIAL (ERP) NA CONSTRUÇÃO CIVIL - Silva, Raymundo Robson Gomes da; Barros Neto, José Barros Neto; Silva Filho, Washington Bastos da; Rocha, Paulo Henrique Gomes da; Ramos, Mibson Michel Santiago; Sousa, Danielle Rodrigues de (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The success of Lean Production has generated several ramifications of Lean Thinking application studies. One of them is Lean Design with intent for waste reduction and improve product development stage. This objective is research is to analyze published articles in Lean Design. The data collection was done in CAPES Journal, Web of Science, ENTAC and IGLC databases. The importance of this study is fueled by the need to know and evaluate the productivity and quality of the most diverse published articles. This research differs from other by addressing not only quantitative but also qualitative methods. To achieve the objectives, this study was divided into two stages, a bibliometric analysis and a textual analysis. The methodology is either quantitative, approaching exploratory nature and statistical of the published periodicals, and also qualitative, by a lexical analysis of the abstracts of all the articles through IRAMUTEQ software. The results show an increasing number of publications and a great diversity of authors and events. The abstracts highlight aspects related to improvement, waste reduction and application in industry and civil construction. The analysis also shows an approach to using tools and design visions such as information flow and value-added generation.